الترويج للسياحة المحلية في مواقع التواصل الاجتماعي - صيفي, مروة; قيطوبي, يمينة (جامعة الوادي - University of Eloued, 2023)
The study aimed to know the role played by social networking sites in promoting local tourism in the state of El-Oued. A publication of the page on Facebook from April 2022 until April 2023 AD، and during our study، we relied on the analytical descriptive method that is commensurate with the nature of the study، in addition to adopting the content analysis method. As for the study tools، we used the content analysis form and the procedures of validity and reliability by applying the Holistic equation and observation The study dealt with a methodological framework and two chapters، the first was devoted to the research، theoretical and applied literature that deals with social networking sites and their role in tourism promotion and the relationship of tourism promotion through social networking sites، while the second chapter dealt with the analytical study of the publications of the akadis travel page in which the data we obtained was analyzed، Which enabled us to reach a set of results، including:The akadis travel page plays an important role in promoting local tourism in the state of El-Oued، through its publications that attract tourists and seek to develop tourism awareness about the region. We also concluded that the public interacts with these publications through positive interactive forms، and the activity of the page via Facebook contributed In the increasing number of tourists towards the region، this is strongly explained by the promotional message of the page about the region، although it is not at the forefront of the page's objectives.
مذكرة ماستر أعلام وأتصال
Keywords: مواقع التواصل الاجتماعي، السياحة المحلية، الترويج السياحي; social networking sites، local tourism، tourism promotion